Independent and combined effects of physical activity and body mass index on the development of Type 2 Diabetes – a meta-analysis of 9 prospective cohort studies. Issue 1 (December 2015) - Cloostermans, Laura; Wendel-Vos, Wanda; Doornbos, Gerda; Howard, Bethany; Craig, Cora; Kivimäki, Mika; Tabak, Adam; Jefferis, Barbara; Ronkainen, Kimmo; Brown, Wendy; Picavet, Susan; Ben-Shlomo, Yoav; et al.
Abstract Background The aim of this harmonized meta-analysis was to examine the independent and combined effects of physical activity and BMI on the incidence of type 2 diabetes. Methods Our systematic literature review in 2011 identified 127 potentially relevant prospective studies of which 9 fulfilled the inclusion criteria (totalN = 117, 878, 56.2 % female, mean age = 50.0 years, range = 25–65 years). Measures of baseline physical activity (low, intermediate, high), BMI-category [BMI < 18.4 (underweight), 18.5–24.9 (normal weight), 25.0–29.9 (overweight), 30+ (obese)] and incident type 2 diabetes were harmonized across studies. The associations between physical activity, BMI and incident type 2 diabetes were analyzed using Cox regression with a standardized analysis protocol including adjustments for age, gender, educational level, and smoking. Hazard ratios from individual studies were combined in a random-effects meta-analysis. Results Mean follow-up time was 9.1 years. A total of 11, 237 incident type 2 diabetes cases were recorded. In mutually adjusted models, being overweight or obese (compared with normal weight) and having low physical activity (compared with high physical activity) were associated with an increased risk of incident type 2 diabetes (hazard ratios 2.33, 95 % CI 1.95–2.78; 6.10, 95 % CI: 4.63–8.04, and 1.23, 95 % CI: 1.09–1.39, respectively). Individuals who were both obese and had low physical activity had 7.4-fold (95 % CI 3.47–15.89) increased risk of type 2 diabetes compared with normal weight, high physically active participants. Conclusions This harmonized meta-analysis shows the importance of maintaining a healthy weight and being physically active in diabetes prevention.